Analisis Dampak Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Festival Suara Indonesia Jakarta Selatan - Muhammad Maulana; Lukman Hakim; Iwan Supriyanto (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2026)
In today’s highly competitive business environment, employee performance is a crucial factor in achieving organizational goals. This study aims to analyze the effect of workload and work environment on employee performance at PT. Festival Suara Indonesia Jakarta Selatan. The research applied a quantitative approach using a survey method. Data were collected from 34 employees through questionnaires and analyzed using SPSS version 27. The analysis techniques included validity and reliability tests, classical assumption tests, and multiple linear regression. The results show that both workload (X1) and work environment (X2) partially have a significant impact on employee performance (Y), as indicated by the t-value of workload 2.999 > t-table 2.040 with a significance of 0.005 < 0.05, and the t-value of work environment 2.356 > t-table 2.040 with a significance of 0.025 < 0.05. Simultaneously, both variables significantly influence employee performance, proven by the F-value of 27.030 > F-table 3.30 and a significance of 0.001 < 0.05. The coefficient of determination (R²) of 0.636 indicates that 63.6% of the variation in employee performance is explained by workload and work environment.